META ANALYSIS: APPLICATION OF THE KNISLEY MATHEMATICS LEARNING MODEL - Yuli Ismayanti; Syamsuri Syamsuri; Maman Fathurrohman; Anwar Mutaqin (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
This study aimed to conduct a meta-analysis of the application of Knisley's mathematical learning model and its impact on students' mathematics abilities. Research begins with formulating a research problem tracking the research results that are relevant for analysis. The data was collected by browsing the electronic journals through Google Scholar, a Garuda portal with the keywords "Knisley mathematical learning model" and "Mathematical ability". From the search, I obtained 86 articles, but relevant only 12 articles from journals that entered the inclusion criteria to be analyzed with the site meta-mar to obtain a large combination effect size. From the interpretation of the measurement of this combined effect, the overall application of the Knisley Model has a strong influence on the student's mathematical abilities. Characteristics of the study were researched in terms of education and years of research. From statistics, if the application of the Knisley Model to improve the ability of the student's mathematical reasoning is influenced by the level of education and years of research